Liquid crystal based low‐loss phase shifter for W‐band frequencies. Issue 23 (1st November 2013) - Jost, M.; Weickhmann, C.; Strunck, S.; Gäbler, A.; Fritzsch, C.; O.H. Karabey,; Jakoby, R.
Abstract : A novel liquid crystal (LC) based hollow waveguide phase shifter with an LC section of 14.6 mm is presented, operating at 80–110 GHz. As a proof‐of‐concept, the phase shifter is biased by using permanent magnets, which results in a differential phase shift of 307°–318° and an insertion loss of 2.1–2.7 dB in the desired frequency range of 99–105 GHz. Hence, a phase shifter figure of merit of 118°–148°/dB is determined, which are to the authors' knowledge the highest values in this frequency range for passive phase shifters.